Learning by Doing and the Dynamic Effects of International Trade - Young, Alwyn (Quarterly Journal of Economics, 1991)
Using an endogenous growth model in which learning by doing, although bounded in each good, exhibits spillovers across goods, this paper investigates the dynamic effects of international trade. Examining an LDC and a DC, the latter distinguished by a higher initial level of knowledge, under autarky and free trade, I find that under free trade the LDC (DC) experiences rates of technical progress and GOP growth less than or equal (greater than or equal) to those enjoyed under autarky. Unless the LDC's population is several orders of magnitude greater than that of the DC and the initial technical gap between the two economies is not large, the LDC will be unable to catch up with its trading partner. Hence, in terms of technical progress and growth, the LDC experiences dynamic losses from trade, whilst the DC experiences dynamic gains. However, since technical progress abroad can improve welfare at home, LDC consumers may enjoy - higher intertemporal utility along the free trade path. In the case of DC consumers, as long as their economy is not overtaken by the LDC they will enjoy both more rapid technical progress and the traditional static gains from trade, and hence experience an unambiguous improvement in intertemporal welfare.